PENGARUH PERDAGANGAN INTERNASIONAL DAN FDI INDONESIA DENGAN AMERIKA, CHINA, DAN JEPANG TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Naufal Nur Maulidi; Sakti, Rachmad Kresna (Journal of Development Economic and Social Studies, 2024)
The purpose of this research is to look at the effect of international trade and FDI from America, China, and Japan on Indonesia's Gross Domestic Product (GDP) from 2000 – 2021. The data used in this research is secondary data sourced from the Central Bureau of Statistics (BPS), Data from the World Bank and the Investment Coordinating Board (BKPM) are in the form of publications that can be accessed on the site. The analytical tool used in this study is a type of quantitative research, namely with multiple linear regression. The research method used in this study is the "Ordinary Least Square (OLS) method". The test results using OLS show that together the net-export and FDI variables have a significant effect on Indonesia's Gross Domestic Product (GDP). While partially, net-exports have a negative and insignificant effect on Indonesia's gross domestic product. Meanwhile, FDI has a positive and significant effect on Indonesia's gross domestic product.